A Nationwide Survey of Lymphangioleiomyomatosis in Korea: Recent Increase in Newly Diagnosed Patients - Park, Hye Yun; Nam, Hae-Seong; Chung, Man Pyo; Jeong, Sung Hwan; Kim, Yu Jin; Cha, Seung-Ick; Kim, Young Whan; Park, Jong Sun; Uh, Soo-Taek; Park, Choon-Sik; Park, Moo Suk; Moon, Ji Ae; et al. (Journal of Korean medical science, 2010)
In 2007, the Korean Interstitial Lung Disease Society had collected clinical data of patients who have diagnosed as Lymphangioleiomyomatosis (LAM) since 1990 through nationwide survey, which showed that LAM patients had increased sharply after 2004. The present study was performed to show the clinical features of Korean patients with LAM, and to establish the reason for the recent increase in the diagnosis. All 63 patients were women and the mean age at diagnosis was 36 yr. The most common presenting symptom was dyspnea and 8 patients had tuberous sclerosis complex. The survival rate at 5 yr after diagnosis was 84%. Compared with patients diagnosed after 2004 (n=34), the patients diagnosed before 2004 (n=29) complained with dyspnea more (P=0.016) and had lower FEV(1)% predicted (P=0.003), and DLco% predicted (P=0.042). The higher proportion of patients diagnosed after 2004 showed the normal chest radiography, and they were detected by routine chest CT screening (P=0.016). This study showed that clinical features of Korean patients with LAM were not different from those reported elsewhere. It is concluded that the reason for the increase of newly diagnosed patients is the result of increase in detection of the early stage LAM by the widespread use of chest CT screening.